Morphological characterization of spinodal decomposition kinetics - Mecke, Klaus; et al. (European Physical Journal B, 1999)
The time evolution of the morphology of homogeneous phases during spinodal decomposition is described using a family of morphological measures known as Minkowski functionals. They provide the characteristic length scale L of patterns in a convenient, statistically robust, and computationally inexpensive way. They also allow one to study the scaling behavior of the content, shape, and connectivity of spatial structures and to define the crossover from the early stage decomposition to the late stage domain growth. We observe the scaling behavior L similar to t(alpha) with alpha = 2/3, alpha = 1/2, and alpha = 1/3 depending on the viscosity of the fluid. When approaching the spinodal density psp: we recover the prediction L similar to (rho - rho(sp))(-1/2) for the early time spinodal decomposition.